The first activation study of the β-carbonic anhydrases from the pathogenic bacteria Brucella suis and Francisella tularensis with amines and amino acids - Andrea Angeli; Sonia Del Prete; Mariana Pinteala; Stelian S. Maier; William A. Donald; Bogdan C. Simionescu; Clemente Capasso; Claudiu T. Supuran (Taylor & Francis Group, 2019)
The activation of the β-class carbonic anhydrases (CAs, EC 4.2.1.1) from the bacteria Brucella suis and Francisella tularensis with amine and amino acids was investigated. BsuCA 1 was sensitive to activation with amino acids and amines, whereas FtuCA was not. The most effective BsuCA 1 activators were L-adrenaline and D-Tyr (KAs of 0.70-0.95 µM). L-His, L-/D-Phe, L-/D-DOPA, L-Trp, L-Tyr, 4-amino-L-Phe, dopamine, 2-pyridyl-methylamine, D-Glu and L-Gln showed activation constants in the range of 0.70-3.21 µM. FtuCA was sensitive to activation with L-Glu (KA of 9.13 µM). Most of the investigated compounds showed a weak activating effect against FtuCA (KAs of 30.5-78.3 µM). Many of the investigated amino acid and amines are present in high concentrations in many tissues in vertebrates, and their role in the pathogenicity of the two bacteria is poorly understood. Our study may bring insights in processes connected with invasion and pathogenic effects of intracellular bacteria.